Announcements of Support and Public Good Provision - Kessler, Judd B. (American Economic Review, 2017)
Providing information about contributions to public goods is known to generate further contributions. However, it is often impossible to provide verifiable information on contributions. Through a large-scale field experiment and a series of laboratory experiments, I show that nonbinding announcements of support for a public good encourage others to contribute, even when actual contributions might not or cannot be made. Providing a way to easily announce support for a charity increases donations by $865 per workplace fundraising campaign (or 16 percent of average giving). I discuss implications for understanding prosocial behavior and for organizations aiming to increase contributions to public goods. (JEL C93, D64, D83, H41, L31)